Curable precursors for structural adhesive compositions containing self-polymerizable toughening agents and methods of using the same
By using a toughener of a radically self-polymerizable material in the structural adhesive, combined with actinization and thermal curing technology, the problem of insufficient impact peeling toughness in the existing technology in the low-temperature environment is solved, and the high-performance bonding effect is achieved under low temperature conditions.
Patent Information
- Application Number
- CN202380061663.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-22
- Filing Date
- 2023-07-18
- Publication Date
- 2025-04-04
AI Technical Summary
The impact peeling toughness of existing structural adhesives in low temperature environments is insufficient, making it difficult to meet the needs of use under low temperature conditions.
A toughening agent containing a free radical self-polymerizable material represented by the formula LR1q is used, and partially cured by actinic irradiation is initiated, and thermal curing of the heat-activated curing agent is formed to form a structural adhesive composition.
The impact peeling toughness of structural adhesives is significantly improved at room temperature and -30°C, ensuring that high performance can be maintained under low temperature conditions.
Smart Images

Figure BDA0005283359720000021 
Figure BDA0005283359720000022 
Figure BDA0005283359720000023
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to curable compositions comprising toughening agents, cured compositions, and related methods. Background Art
[0002] Structural adhesives are known to be used to bond one substrate to another, such as metal to metal, metal to plastic, plastic to plastic, glass to glass. Structural adhesives are an attractive alternative to mechanical joining methods such as riveting or spot welding because they distribute the load stress over a larger area rather than concentrating such stress at a few points. Structural adhesives can also produce cleaner and quieter products because they dampen vibrations and reduce noise. In addition, structural adhesives can be used to bond a variety of materials, sometimes without requiring extensive surface treatment. Summary of the invention
[0003] In a first aspect, a curable precursor of a structural adhesive composition is provided. The curable precursor comprises:
[0004] Epoxy resin;
[0005] a heat-activatable curing agent for the epoxy resin;
[0006] a first toughening agent; and
[0007] The second toughening agent comprises a free radical self-polymerizable material represented by the following formula:
[0008] LR 1 q
[0009] Each R 1 Independently selected from functional groups represented by the following formula:
[0010]
[0011] in:
[0012] Each R 2 are independently hydrogen or methyl;
[0013] n is an integer from 1 to 5, inclusive;
[0014] X is O, S or NH; and
[0015] Y is a single bond or a divalent group represented by the following formula:
[0016]
[0017] in:
[0018] N' is the same as R1 a nitrogen bonded to the carbonyl carbon of
[0019] T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof;
[0020] q is an integer of at least 2; and
[0021] L is a q-valent organic polymer comprising a monomer unit represented by the following formula:
[0022]
[0023] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0024] In a second aspect, a partially cured precursor of a structural adhesive composition is provided. The partially cured precursor comprises:
[0025] Epoxy resin;
[0026] a heat-activatable curing agent for the epoxy resin;
[0027] a first toughening agent; and
[0028] The second toughening agent comprises a self-polymerization reaction product of a free radical self-polymerizable material represented by the following formula:
[0029] LR 1 q
[0030] Each R 1 Independently selected from functional groups represented by the following formula:
[0031]
[0032] in:
[0033] Each R 2 are independently hydrogen or methyl;
[0034] n is an integer from 1 to 5, inclusive;
[0035] X is O, S or NH; and
[0036] Y is a single bond or a divalent group represented by the following formula:
[0037]
[0038] in:
[0039] N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of
[0040] T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof;
[0041] q is an integer of at least 2; and
[0042] L is a q-valent organic polymer comprising a monomer unit selected from the group consisting of monomer units represented by the following formula:
[0043]
[0044] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0045] In a third aspect, a method for making a structural adhesive article is provided. The method comprises:
[0046] a) applying a curable precursor according to the first aspect to a substrate;
[0047] b) partially curing the curable precursor of step a) by initiating a photoinitiator of the free radically self-polymerizable material by actinic irradiation to form a partially cured precursor of a structural adhesive article, the partially cured precursor comprising a polymeric material resulting from the self-polymerization reaction product of the free radically self-polymerizable material; and
[0048] c) substantially fully curing said partially cured precursor of the structural adhesive article obtained in step b) by initiating said heat-activatable curing agent for said epoxy resin, thereby obtaining a substantially fully cured structural adhesive article.
[0049] In a fourth aspect, a method for bonding two components is provided. The method comprises:
[0050] a) applying a curable precursor according to the first aspect or a partially cured precursor according to the second aspect to a surface of at least one of the two components;
[0051] b) joining the two components such that the curable precursor or the partially cured precursor is located between the two components; and
[0052] c) substantially fully curing the partially cured precursor of step a) or c) by initiating the heat-activatable curing agent for the epoxy resin to obtain a substantially fully cured structural adhesive composition and bond the two components.
[0053]
[0026] A further understanding of the features and advantages of the present disclosure will be achieved upon consideration of the detailed description and the appended claims. DETAILED DESCRIPTION
[0054] Glossary
[0055] The term "alkyl" refers to a monovalent group that is a radical of an alkane, which is a saturated hydrocarbon. The alkyl group may be linear, branched, cyclic, or a combination thereof, and typically has 1 to 20 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, and ethylhexyl.
[0056] The term "alkylene" refers to a divalent group that is a radical of an alkane. An alkylene group may be linear, branched, cyclic, or a combination thereof. An alkylene group typically has 1 to 20 carbon atoms. The radical centers of an alkylene group may be on the same carbon atom (i.e., an alkylene group) or on different carbon atoms.
[0057] The term "alkoxy" refers to a monovalent group of formula -OR where R is an alkyl group.
[0058] The term "arylene" refers to a polyvalent aromatic group such as phenylene, naphthylene, and the like.
[0059] The term "heteroalkylene" refers to a group having one or more thio, oxy or -NR b -substituted -CH2-alkylene group, wherein R b is hydrogen or alkyl. The heteroalkylene group may be linear, branched, cyclic, or a combination thereof. Exemplary heteroalkylene groups include alkylene oxides or poly(alkylene oxides). That is, the heteroalkylene group includes at least one group of the formula -(RO)-, wherein R is an alkylene group.
[0060] As used herein, the term "(meth)acrylate" or "(meth)acrylic acid" refers to the corresponding acrylate and methacrylate. Thus, for example, the term "(meth)acrylic acid" encompasses both methacrylic acid and acrylic acid, and the term "(meth)acrylate" encompasses both acrylate and methacrylate. (Meth)acrylate or (meth)acrylic acid may consist of only methacrylate or methacrylic acid, respectively, or may consist of only acrylate or acrylic acid, respectively, but may also relate to mixtures of the corresponding acrylate and methacrylate (or acrylic acid and methacrylic acid).
[0061] In the context of the present disclosure, the expression "free radical self-polymerizable compound" means a compound capable of forming a polymer product (homopolymer) produced by almost complete free radical induced polymerization of the compound with itself, thereby forming a homopolymer. In some cases, radiation exposure is used to generate free radicals. The term "homopolymer" refers herein to one or more polymers produced entirely by polymerization of a single type of monomer.
[0062] In the context of the present disclosure, the expression "the heat-curable resin is substantially uncured" means that less than 10 wt%, less than 5 wt%, less than 2 wt% or even less than 1 wt% of the initial curable resin is unreacted.
[0063] The terms "glass transition temperature" and "Tg" are used interchangeably and refer to the glass transition temperature of a (co)polymer material or mixture of monomers and polymers. Unless otherwise indicated, glass transition temperature values are determined by differential scanning calorimetry (DSC).
[0064] The phrase "at least one of" followed by a list means including any one item in the list and any combination of two or more items in the list. The phrase "at least one of" followed by a list means including any one item in the list and any combination of two or more items in the list.
[0065] As used herein, the term "and / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0066] As used herein, the term "room temperature" refers to a temperature in the range of 20°C to 25°C.
[0067] Epoxy adhesive is widely used structural adhesive, and it not only has some desired mechanical properties, but also has high chemical resistance and aging resistance.But, epoxy adhesive is also often quite brittle, and this makes it necessary to further toughen them.These toughening agents (toughening agent) or toughening agents (toughener) are usually based on the concept of phase separation in epoxy resin matrix.According to the curing cycle, can be by for example using different polar polymers, or by introducing separated phase in the form of core-shell rubber particles to realize toughening in situ during heat curing.For example, the block copolymer with epoxy end group can be suitable as toughening agent.
[0068] It was unexpectedly found that comprising a compound as described in the present disclosure comprising a compound of the formula LR 1 qThe toughening agent of the self-polymerization reaction product of the free radical self-polymerizable material shown in Figure 1 shows improved impact peel toughness not only at room temperature but also at -30°C. Vehicles (e.g., automobiles) can be used at such low ambient temperatures, so higher impact peel toughness at low temperatures is desirable. It was further found that this improvement in impact peel toughness occurs even if the toughening agent is not cross-linked before the epoxy adhesive is thermally cured.
[0069] Curable Precursor
[0070] In a first aspect, the present disclosure provides a curable precursor of a structural adhesive composition. The curable precursor comprises:
[0071] Epoxy resin;
[0072] a heat-activatable curing agent for the epoxy resin;
[0073] a first toughening agent; and
[0074] The second toughening agent comprises a free radical self-polymerizable material represented by the following formula:
[0075] LR 1 q
[0076] Each R 1 Independently selected from functional groups represented by the following formula:
[0077]
[0078] in:
[0079] Each R 2 are independently hydrogen or methyl;
[0080] n is an integer from 1 to 5, inclusive;
[0081] X is O, S or NH; and
[0082] Y is a single bond or a divalent group represented by the following formula:
[0083]
[0084] in:
[0085] N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of
[0086] T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof;
[0087] q is an integer of at least 2; and
[0088] L is a q-valent organic polymer comprising a monomer unit represented by the following formula:
[0089]
[0090] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0091] The curable precursor of the present disclosure can be prepared by methods known to those of ordinary skill in the relevant art. Each of the components of the curable precursor of the structural adhesive composition is described in detail below.
[0092] Epoxy resin
[0093] The curable precursor of the structural adhesive comprises an epoxy resin. Epoxy resins are well known to those skilled in the art of structural adhesive compositions. Suitable epoxy resins for use herein and methods for making the same are fully described in, for example, EP-A1-2 700683 (Elgimiabi et al.) and WO 2017 / 197087 (Aizawa). Exemplary epoxy resins for use herein may advantageously be selected from the group consisting of epoxy novolac resins, bisphenol epoxy resins, hydrogenated epoxy resins, aliphatic epoxy resins, halogenated bisphenol epoxy resins, novolac epoxy resins, and any mixture thereof. Epoxy resins for use in the present disclosure typically include glycidyl groups.
[0094] In some cases, the epoxy resin is selected from the group consisting of novolac epoxy resins, bisphenol epoxy resins (particularly those derived from the reaction of bisphenol A and epichlorohydrin (DGEBA resins)), hydrogenated bisphenol epoxy resins (particularly those derived from the reaction of hydrogenated bisphenol A and epichlorohydrin (hydrogenated DGEBA resins)), and any mixtures thereof.
[0095] According to typical aspects, the curable precursor according to the present disclosure comprises 2 wt % to 50 wt %, 2 wt % to 40 wt %, 3 wt % to 40 wt %, 5 wt % to 30 wt %, 10 wt % to 30 wt %, or even 15 wt % to 30 wt % of the epoxy resin, wherein the weight percentages are based on the total weight of the curable precursor.
[0096] Heat Activated Curing Agent
[0097] The heat-activatable curing agent (e.g., initiator) used for the curable precursor of the present disclosure is not particularly limited. Any heat-activatable curing agent commonly known in the field of structural adhesives for heat-curable epoxy resins can be used in the context of the present disclosure. According to the present disclosure, those skilled in the art can easily identify suitable heat-activatable curing agents for use herein.
[0098] The heat-activatable curing agent used herein can be selected from the group consisting of fast-reacting curing initiators, latent curing initiators, and any combination or mixture thereof. More typically, the heat curing initiator used herein can be selected from the group consisting of fast-reacting thermally initiated curing initiators, latent thermally initiated curing initiators, and any combination or mixture thereof.
[0099] Suitable heat-activatable curing agents may be selected from the group consisting of primary amines, secondary amines, and any combination or mixture thereof. In some cases, the amine used as a heat-activatable curing agent for the curable precursor is selected from the group consisting of aliphatic amines, cycloaliphatic amines, aromatic amines, aromatic structures having one or more amino moieties, polyamines, polyamine adducts, dicyandiamide, and any combination or mixture thereof.
[0100] According to another advantageous aspect of the present disclosure, the heat-activatable curing agent used herein is selected from the group consisting of dicyandiamide, polyamine, polyamine adduct, and any combination or mixture thereof. In a preferred embodiment, the curing agent for the epoxy resin of the present disclosure is selected as dicyandiamide.
[0101] In some cases, the curable precursors of the present disclosure also include a thermal curing accelerator for the thermally curable epoxy resin. Any thermal curing accelerator for the thermally curable resin commonly known in the field of structural adhesives can be used in the context of the present disclosure in a formal manner. According to the present disclosure, those skilled in the art can easily identify suitable thermal curing initiators for use herein.
[0102] Heat-activatable curing agents and thermal curing accelerators are well known to those skilled in the art of structural adhesive compositions. Suitable heat-activatable curing agents and thermal curing accelerators for use herein and methods for making them are fully described in, for example, EP-A1-2700 683 (Elgimiabi et al.) and WO 2017 / 197087 (Aizawa).
[0103] In an advantageous embodiment, suitable thermal curing accelerators for use herein are selected from the group consisting of polyamines, polyamine adducts, ureas, substituted urea adducts, imidazoles, imidazole salts, imidazolines, aromatic tertiary amines, and any combination or mixture thereof. Suitable thermal curing accelerators can be selected from the group consisting of polyamine adducts, substituted ureas, particularly N-substituted urea adducts.
[0104] First toughening agent
[0105] The curable precursor of the present disclosure comprises a first toughening agent. It should be understood that the first toughening agent and the second toughening agent are not the same, but are different materials from each other. The terms "first" and "second" (and optionally "third", "fourth", "fifth", etc.) are only used to distinguish different toughening agents. The first toughening agent that can be used in the present invention is a polymeric compound having both a rubber phase and a thermoplastic phase, such as: a graft polymer having a polymerized diene rubber core and a polyacrylate, polymethacrylate shell; a graft polymer having a polyacrylate rubber core and a polyacrylate or polymethacrylate shell; and elastomer particles polymerized in situ in an epoxide and a copolymerizable polymer stabilizer, the epoxide being derived from a free radical polymerizable monomer.
[0106] Examples of the first class of useful toughening agents include graft copolymers having a polymerized diene rubber backbone or core onto which is grafted a shell of acrylate or methacrylate, monovinyl aromatic hydrocarbon, or mixtures thereof, such as disclosed in US 3,496,250 (Czerwinski), which is incorporated herein by reference. The preferred rubber backbone comprises polymerized butadiene, or a polymerized mixture of butadiene and styrene. The preferred shell comprising polymerized methacrylate is a lower alkyl (C1-C4) substituted methacrylate. Preferred monovinyl aromatic hydrocarbons are styrene, alpha-methylstyrene, vinyltoluene, vinylxylene, ethylvinylbenzene, isopropylstyrene, chlorostyrene, dichlorostyrene, and ethylchlorostyrene.
[0107] An example of a second class of useful toughening agents is an acrylate core-shell graft copolymer, in which the core or backbone is a polyacrylate polymer having a glass transition temperature below about 0°C, such as polybutyl acrylate or poly(ethylhexyl acrylate), onto which is grafted a polymethacrylate polymer (shell) having a glass transition temperature above about 25°C, such as polymethyl methacrylate.
[0108] A third class of toughening agents useful in the curable precursor comprises elastomeric particles having a glass transition temperature (Tg) of less than about 25°C prior to mixing with the other components of the curable precursor. These elastomeric particles are polymerized from free radical polymerizable monomers and copolymerizable polymer stabilizers soluble in the resin. The free radical polymerizable monomers are ethylenically unsaturated monomers or diisocyanates in combination with co-reactive difunctional hydrogen compounds such as diols, diamines, and alkanolamines.
[0109] Useful toughening agents include core / shell polymers such as methacrylate-butadiene-styrene (MBS) copolymers in which the core is a crosslinked styrene / butadiene rubber and the shell is polymethyl acrylate (e.g., ACRYLOID KM653 and KM680 available from Rohm and Haas, Philadelphia, PA), those having a core comprising polybutadiene and a shell comprising poly(methyl methacrylate) (e.g., KANE ACE M511, M521, B11A, B22, B31, and M901 available from Kaneka Corporation, Houston, TX, and CLEARSTRENGTH C223 available from ATOFINA, Philadelphia, PA), those having a polysiloxane core and a polyacrylate shell (e.g., CLEARSTRENGTH 100 from ATOFINA), and those having a polysiloxane core and a polyacrylate shell (e.g., CLEARSTRENGTH 100 from ATOFINA). S-2001 and GENIOPERL P22 available from Wacker-Chemie GmbH, Munich, Germany), those having a polyacrylate core and a poly(methyl methacrylate) shell (e.g., PARALOID EXL2330 available from Rohm and Haas and STAPHYLOID AC3355 and AC3395 available from Takeda Chemical Company, Osaka, Japan), those having an MBS core and a poly(methyl methacrylate) shell (e.g., PARALOID EXL2691A, EXL2691 and EXL2655 available from Rohm and Haas), and the like, and mixtures thereof.
[0110] In select embodiments, the first toughening agent comprises a core-shell rubber.
[0111] The first toughening agent may be used in an amount equal to about 1 to 50 parts by weight, preferably about 3 to 25 parts by weight, relative to 100 parts by weight of the total polymerizable components (including the epoxy resin) of the curable precursor.
[0112] Second toughening agent
[0113] The curable precursor of the present disclosure comprises a second toughening agent. The second toughening agent of the present disclosure comprises a free radical self-polymerizable material represented by the following formula:
[0114] LR1 q
[0115] Each R 1 Independently selected from functional groups represented by the following formula:
[0116]
[0117] in:
[0118] Each R 2 are independently hydrogen or methyl;
[0119] n is an integer from 1 to 5, inclusive;
[0120] X is O, S or NH; and
[0121] Y is a single bond or a divalent group represented by the following formula:
[0122]
[0123] in:
[0124] N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of
[0125] T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof;
[0126] q is an integer of at least 2; and
[0127] L is a q-valent organic polymer comprising a monomer unit represented by formula a):
[0128]
[0129] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0130] In selected embodiments, R 3 is (meth)acrylate and R 1 functional groups.
[0131] With respect to the q-valent organic polymer L, it is understood that L is a homopolymer, rather than a block copolymer or a random copolymer. For example, a homopolymer will contain only one type of monomer unit in the polymer chain, such as a), b), c) or d). The q-valent organic polymer L typically contains 100% by weight of monomer units a).
[0132] Without wishing to be bound by theory, it is believed that the branched chains of the free radically self-polymerizable material interpenetrate with the epoxy resin but do not react with the epoxy resin.
[0133] By LR 1 q (or L 2 R 1 q , L 3 R 1 q , L 4 R 1 q The free radical self-polymerizable materials of the present disclosure represented by , can be prepared by methods known to ordinary technicians in the relevant field and by methods such as, for example, Cooper, SL and Guan, J. (eds.) "Advances in Polyurethane Biomaterials", Chapter 4, (Elsevier Ltd., 2016) and Lin et al., "UV-curable low-surface-energy fluorinated poly(urethane-acrylates) for biomedical applications", "European Polymer Journal", Vol. 44, pp. 2927-2937 (2008). For example, a crosslinker comprising monomer units represented by formula a) and b) can be prepared by the reaction of a polyether primary amine, available under the trade designation DYNAMAR HC-1101 from 3M Company, St. Paul, MN, or as described in U.S. Pat. No. 3,436,359 (Hubin et al.), with 2-isocyanoethyl methacrylate ("IEM").
[0134] In some embodiments, the q-valent organic polymer L has a number average molecular weight of 4000 g / mole to 54000 g / mole relative to polystyrene standards.
[0135] The curable precursors of the present disclosure typically contain 2 wt % or more of the free radical self-polymerizable material described herein, based on the total weight of the curable precursor; 2.25 wt %, 2.5 wt %, 2.75 wt %, 3 wt %, 3.25 wt %, 3.5 wt %, 3.75 wt %, 4 wt %, 4.5 wt % or 5 wt % or more; and 10 wt % or less, 9 wt %, 8 wt %, 7 wt %, 6 wt % or 5 wt % or less of the free radical self-polymerizable material described herein, based on the total weight of the curable precursor.
[0136] Optional components
[0137] The curable precursor according to the present disclosure optionally further comprises additional components, such as a photoinitiator, a reactive diluent, at least one additional toughening agent and / or conventional additives. The additives may include, for example, tackifiers, plasticizers, dyes, pigments, antioxidants, UV stabilizers, corrosion inhibitors, dispersants, wetting agents, adhesion promoters and fillers.
[0138] Fillers that can be used in embodiments of the present disclosure include, for example, fillers selected from the group consisting of microfibrillated polyethylene, fumed silica, talc, wollastonite, aluminosilicate clays (e.g., halloysite), phlogopite, calcium carbonate, kaolin, metal oxides (e.g., barium oxide, calcium oxide, magnesium oxide, zirconium oxide, titanium oxide, zinc oxide), nanoparticle fillers (e.g., nano-silica, nano-zirconia), and combinations thereof.
[0139] Suitable photoinitiators include, for example, free radical polymerization initiators for free radical self-polymerizable second toughening agents, which can be activated by visible light. Free radical polymerization initiators for free radical self-polymerizable second toughening agents are not particularly limited as long as they can be activated by visible light. According to the present disclosure, those skilled in the art can easily identify suitable compounds for use herein.
[0140] Preferably, the photoinitiator is activated by light having a wavelength of at least 350nm. In addition, it is preferred that the photoinitiator is activated by light having a wavelength of at most 750nm. Therefore, it is preferred that the photoinitiator is activated by light having a wavelength in the range of 350nm to 750nm, preferably 380nm to 700nm, more preferably 400nm to 650nm. That is, the photoinitiator can be activated by light having a wavelength in the range of 380nm to 450nm, and / or 450nm to 485nm, and / or 485nm to 500nm, and / or 500nm to 565nm, and / or 565nm to 590nm, and / or 590nm to 625nm, and / or 625nm to 700nm. Particularly preferred herein is blue light, i.e. light having a wavelength of 450nm to 485nm. For example, the photoinitiator can be activated by light having a wavelength in the range of (i) 450 nm to 485 nm, and optionally (ii) 380 nm to 450 nm, 485 nm to 500 nm, 500 nm to 565 nm, 565 nm to 590 nm, 590 nm to 625 nm, and / or 625 nm to 700 nm. Thus, other wavelengths of the visible spectrum of light can be utilized.
[0141] According to a typical aspect of the present disclosure, the photoinitiator of the second free radical self-polymerizable toughening agent is selected from the group consisting of Norrish type (I) free radical polymerization initiator, Norrish type (II) free radical polymerization initiator, and any combination or mixture thereof. According to an advantageous aspect of the present disclosure, the photoinitiator of the second free radical self-polymerizable toughening agent is selected from the group consisting of Norrish type (I) free radical polymerization initiator, and any combination or mixture thereof.
[0142] According to a more advantageous aspect of the present disclosure, the free radical polymerization initiator of the second free radical self-polymerizable toughening agent is selected from α-diketones and / or phosphine oxides, preferably selected from camphorquinone, acylphosphine oxides, phenyl-propanedione, acrylphosphine oxide, dibenzoyl, 1-phenyl-1,2-propanedione and any mixtures and combinations thereof. In some cases, the photoinitiator is preferably camphorquinone.
[0143] In a typical aspect, the curable precursor of the present disclosure comprises no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, no more than 2 wt%, no more than 1 wt%, no more than 0.8 wt%, no more than 0.6 wt%, no more than 0.5 wt%, no more than 0.4 wt%, no more than 0.2 wt%, or even no more than 0.1 wt% of a photoinitiator of a free radical self-polymerizable second toughening agent, wherein the weight percentages are based on the total weight of the curable precursor.
[0144] In another typical aspect, the curable precursor of the present disclosure comprises 0.01 wt % to 10 wt %, 0.01 wt % to 8 wt %, 0.02 wt % to 6 wt %, 0.02 wt % to 5 wt %, 0.02 wt % to 4 wt %, 0.03 wt % to 3 wt %, 0.03 wt % to 2 wt %, 0.03 wt % to 1.8 wt %, 0.03 wt % to 1.6 wt %, 0.03 wt % to 1.5 wt %, 0.03 wt % to 1.4 wt %, or even 0.03 wt % to 1 wt % of a photoinitiator of a free radically self-polymerizable second toughening agent, wherein the weight percentages are based on the total weight of the curable precursor.
[0145] It may be advantageous to use at least one reactive diluent in the curable precursor of the present disclosure. Photoinitiators as described herein may be better soluble in such reactive diluents than in epoxy resins. Therefore, it is preferred that any optional free radical polymerization initiator is dissolved in at least one reactive diluent before mixing with the other components of the curable precursor according to the present disclosure. Reactive diluents are generally known to those skilled in the art in the field of structural adhesives, in particular structural adhesives based on epoxy resins. Preferably, at least one reactive diluent is selected from glycidyl ethers of linear or branched alkanols, preferably from diglycidyl ethers of linear or branched alkyl glycols.
[0146] In some cases, the curable precursor includes at least one or more toughening agents (e.g., a third toughening agent, a fourth toughening agent, etc.). For example, the additional toughening agent may include a compound of formula L 2 R 1 q A free radical self-polymerizable material, wherein R 1 q The LR described in detail above 1 q R 1 q The same, and L 2 is a q-valent organic polymer L comprising a monomer unit b) represented by the following formula 2 :
[0147]
[0148] Where n is an integer from 1 to 5, inclusive, and each R 4 is independently hydrogen or alkyl, and each Z is independently O, S or NH.
[0149] In some cases, the additional toughening agent comprises a 3 R 1 q A free radical self-polymerizable material, wherein R 1q The LR described in detail above 1 q R 1 q The same, and L 3 is a q-valent organic polymer L comprising a monomer unit c) represented by the following formula 3 :
[0150]
[0151] Where n is an integer from 1 to 5, inclusive, and each R 4 is independently hydrogen or alkyl, and each Z is independently O, S or NH.
[0152] In some cases, the additional toughening agent comprises a 4 R 1 q A free radical self-polymerizable material, wherein R 1 q The LR described in detail above 1 q R 1 q The same, and L 4 is a q-valent organic polymer L comprising a monomer unit d) represented by the following formula 4 :
[0153]
[0154] Where R 6 L is hydrogen, a monomer unit selected from the group consisting of monomer units a)-c), or a Z-terminated alkyl chain, wherein the Z-terminated alkyl chain can contain a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein Z is O, S or NH, wherein it is understood that the monomer units of formula d), if they are present, are not located at the end of L.
[0155] Partially cured precursor
[0156] In a second aspect, the present disclosure provides a partially cured precursor of a structural adhesive composition. The partially cured precursor comprises:
[0157] Epoxy resin;
[0158] a heat-activatable curing agent for the epoxy resin;
[0159] a first toughening agent; and
[0160] The second toughening agent comprises a self-polymerization reaction product of a free radical self-polymerizable material represented by the following formula:
[0161] LR 1 q
[0162] Each R 1 Independently selected from functional groups represented by the following formula:
[0163]
[0164] in:
[0165] Each R 2 are independently hydrogen or methyl;
[0166] n is an integer from 1 to 5, inclusive;
[0167] X is O, S or NH; and
[0168] Y is a single bond or a divalent group represented by the following formula:
[0169]
[0170] in:
[0171] N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of
[0172] T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof;
[0173] q is an integer of at least 2; and
[0174] L is a q-valent organic polymer comprising a monomer unit selected from the group consisting of monomer units represented by the following formula:
[0175]
[0176] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0177] The difference between the partially cured precursor and the curable precursor of the first aspect described in detail above is that the second toughener comprises a self-polymerization reaction product of a free radical self-polymerizable material. Therefore, the free radical self-polymerizable material has been polymerized rather than being self-polymerizable. The self-polymerization reaction product of the free radical self-polymerizable material can be formed by exposing the curable precursor to actinic irradiation (e.g., UV irradiation, visible light irradiation, electron beam irradiation or any combination thereof) and / or heat. Typically, the partially cured precursor also comprises a residual photoinitiator for the second toughener. Such residual photoinitiator is a portion of the photoinitiator contained in the curable precursor that is retained after the curable precursor is exposed to actinic irradiation.
[0178] In all other aspects, the components of the partially cured precursor (ie, epoxy resin, heat-activatable curing agent, first toughening agent, second toughening agent, and optional components) are as described in detail above with respect to the first aspect.
[0179] According to a typical aspect of the partially cured precursor according to the present disclosure, the polymer material comprising the self-polymerization reaction product of the free radical self-polymerizable material is substantially completely polymerized, and in particular has a degree of polymerization of more than 90%, more than 95%, more than 98% or even more than 99%. Since the polymer material comprising the self-polymerization reaction product of the free radical self-polymerizable material is substantially completely polymerized, the polymerization reaction advantageously has a fixed and irreversible end and does not trigger any reaction that shortens the shelf life in the remaining part of the curable precursor. It is believed that this feature advantageously affects the overall shelf life of the curable precursor.
[0180] In one advantageous aspect, the partially cured precursor according to the present disclosure has a glass transition temperature (Tg) of no greater than 0°C, no greater than -5°C, no greater than -10°C, no greater than -15°C, or even no greater than -20°C, when measured by DSC.
[0181] In another advantageous aspect of the present disclosure, the partially cured precursor has an elongation at break of at least 50%, at least 80%, at least 100%, at least 150%, or even at least 200%, when measured according to the tensile test DIN EN ISO 527. This particular property makes the partially cured precursor and the resulting structural adhesive suitable for automated processing and application, especially automated processing and application by high-speed robotic equipment. More particularly, the partially cured precursor and the resulting structural adhesive of the present disclosure enable efficient automation of the process of forming a metal joint between metal sheets.
[0182] method
[0183] In a third aspect, a method for making a structural adhesive article is provided. The method comprises:
[0184] a) applying a curable precursor according to the first aspect to a substrate;
[0185] b) partially curing the curable precursor of step a) by initiating a photoinitiator of the free radically self-polymerizable material by actinic irradiation to form a partially cured precursor of a structural adhesive article, the partially cured precursor comprising a polymeric material resulting from the self-polymerization reaction product of the free radically self-polymerizable material; and
[0186] c) substantially fully curing said partially cured precursor of the structural adhesive article obtained in step b) by initiating said heat-activatable curing agent for said epoxy resin, thereby obtaining a substantially fully cured structural adhesive article.
[0187] The curable precursor is as described in detail above with respect to the first aspect, including any of the various embodiments described therein. The curable precursor is particularly suitable for carrying out an overall curing mechanism involving a two-stage reaction, whereby two polymer networks are formed sequentially.
[0188] In the first stage reaction (B stage), the free radical self-polymerizable material self-polymerizes when initiated by a free radical polymerization initiator for the free radical self-polymerizable material, thereby forming a polymer material of the self-polymerization reaction product containing the polymerizable material, and the polymerizable material contains the self-polymerizable material. Generally, the temperature T1 of the free radical polymerization initiator for the free radical self-polymerizable multifunctional compound is not enough to cause the initiation of the heat-activated curing agent of the heat-curable resin (that is, epoxy resin and any other curable material, such as reactive diluent). Therefore, the first stage reaction usually produces a partially cured precursor, wherein the heat-curable resin is substantially uncured, and is particularly embedded in the polymer material of the self-polymerization reaction product containing the polymerizable material, and the polymerizable material contains the self-polymerizable material.
[0189] The first stage reaction is generally referred to as a film-forming reaction, which generally results in a phase change in the initial curable precursor, particularly because the polymer material comprising the self-polymerization reaction product of the self-polymerizable material provides structural integrity to the initial curable precursor. Advantageously, the first stage reaction generally does not require any significant energy input.
[0190] Photoinitiators can be initiated by exposure to actinic irradiation, such as by light initiation with a wavelength in the range of 350nm to 750nm, as described in detail above for suitable photoinitiators for curable precursors. When compared with UV light activation commonly used to initiate adhesive curing in industrial applications, it is particularly advantageous to use light in the visible spectrum of light (especially blue light) to activate free radical polymerization initiators. Not only is the penetration of visible light (especially blue light) higher, the reaction also tends to proceed much faster than with UV-A light. Although the former has the advantage of being able to generate thicker films, the latter has the advantage of generally being able to manufacture films faster. In addition, the EHS problems of using UV light at the manufacturing site can be avoided.
[0191] The partially cured precursor may generally take the form of a film-like self-supporting composition or multidimensional object having dimensional stability, which allows it to be pre-applied to a selected substrate, in particular a liner, until further processing. In selected cases, the above method further comprises removing the partially cured precursor of the structural adhesive article obtained in step b) or the substantially fully cured structural adhesive article obtained in step c) from the substrate.
[0192] The partially cured precursors generally have excellent characteristics and properties with respect to elasticity, adhesion, cold flow and surface wettability. It is believed that the free radical self-polymerizable material of the second toughening agent plays a key role in obtaining the advantageous properties of the partially cured precursors as described above. Advantageously, the partially cured precursors can be appropriately shaped to meet the requirements of any particular application.
[0193] The second stage reaction (A stage) occurs after the first stage reaction and involves thermally curing the heat-curable resin (i.e., epoxy resin and any other curable materials, e.g., reactive diluents) when thermally initiated by a suitable heat-activatable curing agent at a temperature T2, typically higher than temperature T1. This reaction step typically results in the formation of a polymer product resulting from thermal curing of the heat-curable resin, particularly from (co)polymerization of the heat-curable resin and a heat-activatable curing agent for the heat-curable resin.
[0194] In the context of the present disclosure, the expression "substantially fully cured curable precursor" or "substantially fully cured partially cured precursor" is intended to express that as a result of the polymerization / curing step, greater than 90 weight %, greater than 95 weight %, greater than 98 weight % or even greater than 99 weight % of the total amount of thermally curable resin and free radically self-polymerizable material is polymerized / cured.
[0195] The curable precursors of the present disclosure generally rely on the above-mentioned dual-cure system / hybrid-cure system, which involves two independent reaction systems activated with different triggering steps to ensure that the above-mentioned two-stage reaction is carried out in a sequential manner. Advantageously, the curable precursors of the present disclosure can be partially cured (or pre-cured) and pre-applied on a selected substrate, and then finally cured in situ to produce a structural adhesive with excellent characteristics directly on the desired substrate or article.
[0196] According to an advantageous aspect, the curable precursor or partially or fully cured structural adhesive composition of the present disclosure is formed into an elongated film form. The elongated film shape is a conventional and convenient shape to pre-apply the structural adhesive to a selected substrate, particularly a liner, prior to further processing.
[0197] In a particular aspect of the present disclosure, the elongated films used herein have a thickness greater than 500 microns, greater than 600 microns, greater than 700 microns, greater than 800 microns, greater than 900 microns, or even greater than 1000 microns.
[0198] In another particular aspect of the present disclosure, the elongated films used herein have a thickness of no greater than 500 microns, no greater than 400 microns, no greater than 300 microns, no greater than 200 microns, no greater than 100 microns, or even greater than 50 microns.
[0199] While an elongated film shape may be convenient in many different applications, this particular shape is not always satisfactory for adhesively bonding components having complex three-dimensional configurations or topologies, particularly when there are challenging bonding areas or surfaces.
[0200] Therefore, on the other hand, the curable precursor of the present disclosure or the (mixed) structural adhesive composition that is partially or completely cured can be formed into the form of a three-dimensional object. Suitable three-dimensional object shapes for this article will be widely changed according to the specific configuration of target bonding application and assembly to be bonded, particularly bonding area. According to the present disclosure, those skilled in the art will easily identify the exemplary three-dimensional object shapes for this article. According to an exemplary aspect of the present disclosure, the three-dimensional object has a shape selected from the group consisting of circular, semicircular, elliptical, square, rectangular, triangle, trapezoidal, polygonal shape or their arbitrary combination. In the context of the present disclosure, the shape of the three-dimensional object is intended to refer to the shape of the three-dimensional object part according to the direction of the maximum size of the three-dimensional object that is substantially perpendicular to the three-dimensional object in this article.
[0201] On the other hand, the present disclosure relates to a composite product comprising a curable precursor as described above or a partially or completely cured (mixed) structural adhesive composition applied to at least a portion of the surface of the product. Suitable surfaces and products for use herein are not particularly limited. Any surface, product, substrate and material generally known to be suitable for use in combination with a structural adhesive composition can be used in the context of the present disclosure.
[0202] In a typical aspect, the article used herein comprises at least one component, particularly a metal or composite component. In an advantageous aspect, the composite article according to the present disclosure is used in body-in-white bonding applications in the automotive industry, particularly for hemming flange bonding of components, more particularly metal or composite components; and for structural bonding operations in the aviation and aerospace industry.
[0203] In a fourth aspect, a method for bonding two components is provided. The method comprises:
[0204] a) applying a curable precursor according to the first aspect or a partially cured precursor according to the second aspect to a surface of at least one of the two components;
[0205] b) joining the two components such that the curable precursor or the partially cured precursor is located between the two components; and
[0206] c) substantially fully curing the partially cured precursor of step a) by initiating the heat-activatable curing agent for the epoxy resin to obtain a substantially fully cured structural adhesive composition and bond the two components.
[0207] According to an advantageous aspect of the method for bonding two parts, the two parts are metal parts. According to another advantageous aspect, the method for bonding two parts is used for hemming flange bonding of metal parts, wherein:
[0208] - the partially cured precursor is formed into the form of an elongated film;
[0209] - the partially cured precursor film has a first portion proximate a first end of the precursor film and a second portion proximate a second end opposite the thermosetting resin first end of the precursor film;
[0210] - the first metal portion comprises a first metal panel having a first body portion and a first flange portion along an edge of the first body portion adjacent to a first end of the first body portion;
[0211] - the second metal portion comprises a second metal panel having a second body portion and a second flange portion along an edge of the second body portion adjacent to a second end of the second body portion;
[0212] The method comprises the following steps:
[0213] a) adhering the partially cured precursor film to the first metal panel or the second metal panel, whereby after adhering and folding, a metal joint is obtained, wherein the partially cured precursor film is folded such that:
[0214] i. a first portion of the partially cured precursor film is disposed between the second flange of the second metal panel and the first body portion of the first metal panel, and
[0215] ii. a second portion of the partially cured precursor film is disposed between the first flange of the first metal panel and the second body portion of the second metal panel; and
[0216] b) substantially fully curing the partially cured precursor by initiating a thermal cure initiator for the thermally curable resin to obtain a substantially fully cured (hybrid) structural adhesive composition and bond the metal joint.
[0217] According to still another advantageous aspect of the method of bonding two components, one side of the first edge portion of the first metal component is folded back and a hemming flange structure is formed so as to sandwich the second metal component, and a curable precursor or a partially cured precursor as described above is provided so as to adhere at least the first edge portion of the first metal component and the first surface side of the second metal component to each other.
[0218] Methods for bonding two parts, in particular for hemming flange bonding of metal parts, are well known to those skilled in the art of structural adhesive compositions. Suitable methods for bonding two parts herein are fully described in, for example, EP-A1-2 700 683 (Elgimiabi et al.) and WO 2017 / 197087 (Aizawa).
[0219] In particular aspects of the present disclosure, the substrates, components and surfaces used in these methods comprise a metal selected from the group consisting of aluminum, steel, iron and any mixture, combination or alloy thereof. More advantageously, the substrates, components and surfaces used herein comprise a metal selected from the group consisting of aluminum, steel, stainless steel and any mixture, combination or alloy thereof. In a particularly advantageous embodiment of the present disclosure, the substrates, components and surfaces used herein comprise aluminum.
[0220] It has also been surprisingly discovered that, in some embodiments, the curable precursors described above are suitable for making structural adhesive compositions having excellent characteristics and performance in terms of adhesion to oil-contaminated substrates such as stainless steel and aluminum.
[0221] Selected Embodiments of the Disclosure
[0222] In a first embodiment, a curable precursor of a structural adhesive composition is provided. The curable precursor comprises an epoxy resin; a heat-activatable curing agent for the epoxy resin; a first toughening agent; and a second toughening agent, wherein the second toughening agent comprises a free radical self-polymerizable material represented by the following formula: LR 1 q ; where each R 1 Independently selected from functional groups represented by the following formula:
[0223]
[0224] Each R 2 are independently hydrogen or methyl; n is an integer from 1 to 5, inclusive; X is O, S or NH; and Y is a single bond or a divalent group represented by the formula:
[0225]
[0226] Where N' is the same as R 1 The nitrogen bonded to the carbonyl carbon of the carbonyl carbon; and T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof; q is an integer of at least 2; and L is a monomer unit represented by formula a)
[0227] Q-valent organic polymers:
[0228]
[0229] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0230] In a second embodiment, there is provided a curable precursor according to the first embodiment, further comprising at least one reactive diluent.
[0231] In a third embodiment, there is provided a curable precursor according to the second embodiment, wherein the at least one reactive diluent comprises a glycidyl ether of a linear or branched alkanol.
[0232] In a fourth embodiment, there is provided a curable precursor according to any one of the first to third embodiments, further comprising a photoinitiator activated by light having a wavelength in the range of 350 nm to 750 nm.
[0233] In a fifth embodiment, a curable precursor according to any one of the first to fourth embodiments is provided, wherein the first toughening agent comprises a core-shell rubber.
[0234] In a sixth embodiment, there is provided a curable precursor according to any one of the first to fifth embodiments, wherein the heat-activatable curing agent for the epoxy resin is selected from the group consisting of dicyandiamide, polyamines, polyamine adducts, and any combination thereof.
[0235] In a seventh embodiment, a curable precursor according to any one of the first to sixth embodiments is provided, wherein the q-valent organic polymer L has a number average molecular weight of 4000 to 54000 g / mole relative to polystyrene standards.
[0236] In an eighth embodiment, a curable precursor according to any one of the first to seventh embodiments is provided, wherein the curable precursor further comprises a third toughening agent, wherein the third toughening agent comprises a compound of formula L 2 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 2 is a q-valent organic polymer L comprising a monomer unit b) represented by the following formula 2 :
[0237]
[0238] Where n is an integer from 1 to 5, inclusive, and each R 4 are independently hydrogen or alkyl,
[0239] And each Z is independently O, S or NH.
[0240] In a ninth embodiment, a curable precursor according to any one of the first to eighth embodiments is provided, wherein the curable precursor further comprises a fourth toughening agent, wherein the fourth toughening agent comprises a compound of formula L 3 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 3is a q-valent organic polymer L comprising a monomer unit c) represented by the following formula 3 :
[0241]
[0242] Where n is an integer from 1 to 5, inclusive, and each R 4 are independently hydrogen or alkyl,
[0243] And each Z is independently O, S or NH.
[0244] In a tenth embodiment, a curable precursor according to any one of the first to ninth embodiments is provided, wherein the curable precursor further comprises a fifth toughening agent, wherein the fifth toughening agent comprises a compound of formula L 4 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 4 is a q-valent organic polymer L comprising a monomer unit d) represented by the following formula 4 :
[0245]
[0246] Where R 6 is hydrogen, a monomer unit selected from the group consisting of monomer units a) to c), or a Z-terminated alkyl chain, wherein the Z-terminated alkyl chain can contain a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and a combination thereof, and wherein Z is O, S, or NH.
[0247] In an eleventh embodiment, a curable precursor according to any one of the first to tenth embodiments is provided, wherein R 3 is (meth)acrylate and R 1 functional groups.
[0248] In a twelfth embodiment, there is provided a curable precursor according to any one of the first to eleventh embodiments, wherein the q-valent organic polymer L comprises 100 wt% of monomer units a) monomer.
[0249] In a thirteenth embodiment, a curable precursor according to any one of the first to twelfth embodiments is provided, wherein the second toughening agent is present in an amount of up to 10 wt % based on the total weight of the curable precursor.
[0250] In a fourteenth embodiment, a partially cured precursor of a structural adhesive composition is provided. The partially cured precursor comprises an epoxy resin; a heat-activatable curing agent for the epoxy resin; a first toughening agent; and a second toughening agent, wherein the second toughening agent comprises a self-polymerization reaction product of a free-radical self-polymerizable material represented by the following formula: LR 1 q ; where each R 1 Independently selected from functional groups represented by the following formula:
[0251]
[0252] Each R 2 are independently hydrogen or methyl; n is an integer from 1 to 5, inclusive; X is O, S or NH; and Y is a single bond or a divalent group represented by the formula:
[0253]
[0254] Where N' is the same as R 1 wherein the carbonyl carbon of the nitrogen is bonded to the carbonyl carbon of the nitrogen; and T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof; q is an integer of at least 2; and L is a q-valent organic polymer comprising a monomer unit selected from the group consisting of monomer units represented by the following formula:
[0255]
[0256] Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
[0257] In a fifteenth embodiment, a partially cured precursor according to the fourteenth embodiment is provided, further comprising residual photoinitiator for the second toughening agent.
[0258] In the sixteenth embodiment, a method for manufacturing a structural adhesive article is provided. The method includes a) applying a curable precursor according to any one of the first embodiment to the thirteenth embodiment to a substrate; b) partially curing the curable precursor of step a) by initiating the photoinitiator of the free radical self-polymerizable material by actinic irradiation, thereby forming a partially cured precursor of a structural adhesive article, the partially cured precursor comprising a polymer material produced by the self-polymerization reaction product of the free radical self-polymerizable material; and c) substantially completely curing the partially cured precursor of the structural adhesive article obtained in step b) by initiating the heat-activatable curing agent for the epoxy resin, thereby obtaining a substantially completely cured structural adhesive article.
[0259] In a seventeenth embodiment, a method according to the sixteenth embodiment is provided, further comprising removing the partially cured precursor of the structural adhesive article obtained in step b) or the substantially fully cured structural adhesive article obtained in step c) from the substrate.
[0260] In an eighteenth embodiment, a method for bonding two parts is provided. The method comprises a) applying a curable precursor or a partially cured precursor according to any one of the first embodiment to the fifteenth embodiment to the surface of at least one of the two parts; b) joining the two parts so that the curable precursor or the partially cured precursor is located between the two parts; and c) substantially completely curing the partially cured precursor of step a) by initiating the heat-activatable curing agent for the epoxy resin, thereby obtaining a substantially completely cured structural adhesive composition and bonding the two parts.
[0261] In a nineteenth embodiment, a method according to the eighteenth embodiment is provided, the method further comprising, before step c), partially curing the curable precursor of step a) by initiating a photoinitiator of the free radical self-polymerizable material by actinic irradiation, thereby forming a partially cured precursor of the structural adhesive article, wherein the partially cured precursor comprises a polymer material produced by the self-polymerization reaction product of the free radical self-polymerizable material.
[0262] Objects and advantages of this disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.
[0263] Example
[0264] Unless otherwise indicated, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight.
[0265] Materials used in the examples
[0266]
[0267]
[0268] Test methods for one-component adhesives
[0269] Preparation of formulations for testing :
[0270] KaneAce MX 153, KaneAce MX 257, Epikote 1001 and KaneAce B564 were placed in a beaker, which was placed in a high-speed mixer (DAC 150.1FVZ Speedmixer, Hauschild Engineering, Germany) at 3500 rpm for 5 minutes. The mixture was cooled and the process was repeated several times until the solid part was completely and evenly mixed. Then, Epikote 828 and ipox RD24 were added to the mixture and mixed at 3500 rpm for 1 minute. Subsequently, a toughening agent containing a free radical self-polymerizable material as specified in Table 1 was mixed, which toughening agent must be heated to 80° C. in some cases to liquefy, followed by dicyandiamide (DICY) and finally camphorquinone. From then on, the mixture was kept dark to avoid premature curing of the B stage or quenching of camphorquinone.
[0271]
[0272] Preparation of test samples :
[0273] After the preparation, the material was extruded between two PETSilphan liners in the shape of a 0.3 mm thick film by using a knife coater. The extruded film was illuminated with a blue LED array (10 cm×10 cm; 460 nm; available from Dr. Bosideng Corporation (Dr. Opsitec) for 30 seconds until the B stage reaction is complete.
[0274] Preparation of test specimens for lap shear strength (OLS) testing, T-peel testing, and impact peel testing :
[0275] The surfaces of OLS, T-peel and impact peel samples (steel, grade DC04 ZE 75RL2027) were cleaned with n-heptane and coated with 3 g / m 2The test samples were coated with a test oil (PL3802-39S commercially available from Fuchs Petrolub AG, Germany). Prior to testing, the test samples were placed at ambient room temperature (23°C + / - 2°C, 50% relative humidity + / - 5%) for 24 hours, and OLS, T peel and impact peel strength were measured as described below.
[0276] 1 ) Lap shear strength (OLS) according to DIN EN 1465 .
[0277] According to DIN EN 1465, the lap shear strength is determined using a Zwick Z050 tensile tester (commercially available from Zwick GmbH & Co. KG, Ulm, Germany) running at a chuck speed of 10 mm / min. In order to prepare the lap shear strength test assembly, the extruded film produced by blue light irradiation is cut into a rectangular shape and applied to one surface of the test panel to obtain a limiting layer with a thickness of 0.3 mm. The sample is then covered with a second steel strip to form a 13 mm lap joint. The lap joint is then clamped together using two binder clips, and the test assembly is further stored at room temperature for 4 hours after bonding, and then placed in an air circulation oven at 180 ° C for 30 minutes. The next day, the sample is tested. For each of the embodiments, five samples are measured, and the results are averaged and reported in megapascals (MPa).
[0278] 2) T peel strength according to DIN EN ISO 11339 .
[0279] According to DIN EN ISO 11339, the T peel strength is determined using a Zwick Z050 tensile tester (commercially available from Zwick, Ulm, Germany) running at a crosshead speed of 100 mm / min. In order to prepare the T peel strength test assembly, the extruded film produced by blue light irradiation is cut into a rectangular shape and applied to one surface of the test panel to obtain a limiting layer with a thickness of 0.3 mm. The second test panel surface is then bonded to the first test panel surface to form a 100 mm lap joint. The samples are fixed together with a clip and first stored at room temperature for 12 hours, and then placed in an air circulation oven at 180 ° C for 30 minutes. The next day, the sample is tested. For each of the embodiments, three samples are measured, and the results are averaged and reported in Newtons (N).
[0280] 3) Impact peel strength according to DIN EN ISO 11343 .
[0281] Impact peeling properties were determined using a Zwick HIT450P pendulum tester (commercially available from Zwick, Ulm, Germany) according to DIN EN ISO 11343. To prepare the impact peeling test assembly, the extruded film produced by blue light irradiation was cut into a rectangular shape and applied to one surface of the test panel to obtain a defined layer with a thickness of 0.3 mm. The second test panel surface was then bonded to the first test panel surface to form a 30 mm lap joint. The samples were fixed together with a clamp and first stored at room temperature for 12 hours and then placed in an air circulation oven at 180°C for 30 minutes. The next day, the samples were tested. The substrates were bonded over a length of 30 mm and the free arms of the specimens were clamped. The wedge was pulled through the bonded portion of the specimen at a test rate of 2 m / s. The results were averaged and reported in N / mm, indicating the resistance of the adhesive to the effects of crack growth at different temperatures. Ten samples were prepared for each test; five samples were tested at room temperature and five samples were tested at -30°C. The test results of the formulations are shown in Table 2.
[0282] As can be seen from the results shown in Table 2, the structural adhesives according to the present disclosure provide improved impact peel strength performance on oily contaminated substrates when compared to the comparative examples formulated without a second toughening agent comprising a free radical self-polymerizable material. This improvement can be particularly seen when tested at low temperatures (-30°C), where the examples show only a slight drop in performance compared to testing at room temperature. In contrast, it is expected that Comparative Examples 1 and 4 (which do not contain any photo-initiated self-polymerizable monomer or any polymerization initiator thereof) show a significant loss in impact peel strength on oily contaminated substrates when tested at low temperatures and compared to values at room temperature.
[0283] Table 2
[0284]
[0285] All references, patents and patent applications cited in the above patent applications are incorporated herein by reference in their entirety in a consistent manner. In the event of inconsistency or conflict between the incorporated references and the present application, the information in the foregoing description shall prevail. The foregoing description, which is given to enable a person of ordinary skill in the art to practice the present disclosure protected by the claims, should not be construed as limiting the scope of the present disclosure, which is defined by the claims and all equivalents thereof.
Claims
1. A curable precursor for a structural adhesive composition, the curable precursor comprising: Epoxy resin; a heat-activatable curing agent for the epoxy resin; a first toughening agent; and The second toughening agent comprises a free radical self-polymerizable material represented by the following formula: LR 1 q Each R 1 Independently selected from functional groups represented by the following formula: in: Each R 2 are independently hydrogen or methyl; n is an integer from 1 to 5, inclusive; X is O, S or NH; and Y is a single bond or a divalent group represented by the following formula: in: N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof; q is an integer of at least 2; and L is a q-valent organic polymer comprising a monomer unit represented by formula a): Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
2. The curable precursor according to claim 1, further comprising at least one reactive diluent.
3. The curable precursor according to claim 2, wherein the at least one reactive diluent comprises a glycidyl ether of a linear or branched alkanol.
4. The curable precursor according to any one of claims 1 to 3, further comprising a photoinitiator activated by light having a wavelength in the range of 350 nm to 750 nm.
5. The curable precursor according to any one of claims 1 to 4, wherein the first toughening agent comprises a core-shell rubber.
6. The curable precursor according to any one of claims 1 to 5, wherein the heat-activatable curing agent for the epoxy resin is selected from the group consisting of dicyandiamide, polyamines, polyamine adducts and any combination thereof.
7. The curable precursor according to any one of claims 1 to 6, wherein the q-valent organic polymer L has a number average molecular weight of 4000 to 54000 g / mol relative to polystyrene standards.
8. The curable precursor according to any one of claims 1 to 7, further comprising a third toughening agent, wherein the third toughening agent comprises a compound of formula L 2 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 2 is a q-valent organic polymer L comprising a monomer unit b) represented by the following formula 2 : Where n is an integer from 1 to 5, inclusive, and each R 4 is independently hydrogen or alkyl, and each Z is independently O, S or NH.
9. The curable precursor according to any one of claims 1 to 8, further comprising a fourth toughening agent, wherein the fourth toughening agent comprises a compound of formula L 3 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 3 is a q-valent organic polymer L comprising a monomer unit c) represented by the following formula 3 : Where n is an integer from 1 to 5, inclusive, and each R 4 is independently hydrogen or alkyl, and each Z is independently O, S or NH.
10. The curable precursor according to any one of claims 1 to 9, further comprising a fifth toughening agent, wherein the fifth toughening agent comprises a compound of formula L 4 R 1 q A free radical self-polymerizable material, wherein R 1 q With LR 1 q R 1 q The same, and L 4 is a q-valent organic polymer L comprising a monomer unit d) represented by the following formula 4 : Where R 6 is hydrogen, a monomer unit selected from the group consisting of monomer units a) to c), or a Z-terminated alkyl chain, wherein the Z-terminated alkyl chain can contain a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and a combination thereof, and wherein Z is O, S, or NH.
11. A curable precursor according to any one of claims 1 to 10, wherein R 3 is (meth)acrylate and is R 1 functional groups.
12. The curable precursor according to any one of claims 1 to 11, wherein the q-valent organic polymer L comprises 5 to 20 wt% of monomer units a) monomers.
13. The curable precursor according to any one of claims 1 to 12, wherein the second toughening agent is present in an amount of up to 10 wt% based on the total weight of the curable precursor.
14. A partially cured precursor of a structural adhesive composition, the partially cured precursor comprising: Epoxy resin; a heat-activatable curing agent for the epoxy resin; a first toughening agent; and The second toughening agent comprises a self-polymerization reaction product of a free radical self-polymerizable material represented by the following formula: LR 1 q Each R 1 Independently selected from functional groups represented by the following formula: in: Each R 2 are independently hydrogen or methyl; n is an integer from 1 to 5, inclusive; X is O, S or NH; and Y is a single bond or a divalent group represented by the following formula: in: N' is the same as R 1 a nitrogen bonded to the carbonyl carbon of T is a divalent group selected from the group consisting of a linear alkylene group, a cyclic alkylene group, an unsubstituted arylene group, a substituted arylene group, and a combination thereof; q is an integer of at least 2; and L is a q-valent organic polymer comprising a monomer unit selected from the group consisting of monomer units represented by the following formula: Where R 3 is hydrogen, a (meth)acrylate group, or a Z-terminated alkyl or heteroalkylene chain, wherein each Z-terminated chain can independently comprise a bond selected from the group consisting of a secondary amino bond, a tertiary amino bond, an ether bond, and combinations thereof, and wherein each Z is independently O, S, or NH.
15. The partially cured precursor of claim 14, further comprising residual photoinitiator for the second toughening agent.
16. A method of making a structural adhesive article, the method comprising: a) applying a curable precursor according to any one of claims 1 to 13 to a substrate; b) partially curing the curable precursor of step a) by initiating a photoinitiator of the free radically self-polymerizable material by actinic irradiation, thereby forming a partially cured precursor of a structural adhesive article, the partially cured precursor comprising a polymeric material produced from the self-polymerization reaction product of the free radically self-polymerizable material; as well as c) substantially fully curing said partially cured precursor of the structural adhesive article obtained in step b) by initiating said heat-activatable curing agent for said epoxy resin, thereby obtaining a substantially fully cured structural adhesive article.
17. The method of claim 16, further comprising removing the partially cured precursor of the structural adhesive article obtained in step b) or the substantially fully cured structural adhesive article obtained in step c) from the substrate.
18. A method of bonding two parts, the method comprising: a) applying a curable precursor or a partially cured precursor according to any one of claims 1 to 15 to a surface of at least one of the two components; b) joining the two components such that the curable precursor or the partially cured precursor is located between the two components; as well as c) substantially fully curing the partially cured precursor of step a) by initiating the heat-activatable curing agent for the epoxy resin to obtain a substantially fully cured structural adhesive composition and bond the two components.
19. The method according to claim 18 further comprises, before step c), partially curing the curable precursor of step a) by initiating a photoinitiator of the free radical self-polymerizable material by actinic irradiation, thereby forming a partially cured precursor of the structural adhesive article, wherein the partially cured precursor comprises a polymer material produced by the self-polymerization reaction product of the free radical self-polymerizable material.
Citation Information
Patent Citations
Polyether polyprimary polyamines and elastomeric products thereof
US3436359A
Blends of epoxy resins and acrylonitrile butadiene-styrene graft copolymers
US3496250A
Structural adhesive film, metal member assembly, and method for manufacturing the same
WO2017197087A1